2014
DOI: 10.5851/kosfa.2014.34.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Myosin Heavy Chain Isoforms from Longissimus Thoracis Muscle of Hanwoo Steer by Electrophoresis and LC-MS/MS

Abstract: The purpose of this study was to analyze myosin heavy chain (MHC) isoforms in bovine longissimus thoracis (LT) muscle by liquid chromatography (LC) and mass spectrometry (MS). LT muscles taken from Hanwoo (Korean native cattle) steer (n=3) used to separate myosin bands by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The peptide queries were obtained from the myosin bands by LC-MS/MS analysis following in-gel digestion with trypsin. A total of 33 and 43 queries were identified as common and unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Previously, three fiber types, I, IIA, and IIX (or IIB), were observed in bovine muscles (Hwang et al, 2010;Kim et al, 2016;Ozawa et al, 2000), whereas hybrid fiber types were not frequently identified (Moreno-Sanchez et al, 2008;Greenwood et al, 2009). Fiber type IIB and hybrid type IIX+IIB were not detected in bovine muscle because of the lack of MHC 2b in major bovine muscles (LT, PM, and SM), as previously reported (Kim, 2014;Kim et al, 2016). Muscle fiber composition showed a similar trend to the results of previous reports (Hwang et al, 2010;Ozawa et al, 2000).…”
Section: Muscle Fiber Characteristicssupporting
confidence: 85%
“…Previously, three fiber types, I, IIA, and IIX (or IIB), were observed in bovine muscles (Hwang et al, 2010;Kim et al, 2016;Ozawa et al, 2000), whereas hybrid fiber types were not frequently identified (Moreno-Sanchez et al, 2008;Greenwood et al, 2009). Fiber type IIB and hybrid type IIX+IIB were not detected in bovine muscle because of the lack of MHC 2b in major bovine muscles (LT, PM, and SM), as previously reported (Kim, 2014;Kim et al, 2016). Muscle fiber composition showed a similar trend to the results of previous reports (Hwang et al, 2010;Ozawa et al, 2000).…”
Section: Muscle Fiber Characteristicssupporting
confidence: 85%
“…More recently, Moran et al and Gagaoua and co-workers from two different studies , found that the MyHC IIb isoform is present in very few animals only within very different groups of rearing practices and production systems. Using a proteomics-based approach following in-gel digestion with trypsin by LC-MS/MS mass spectrometry, Kim identified peptides specific to MyHC I, IIa, and IIx but did not identify a unique peptide of MyHC IIb in Longissimus thoracis muscle of Korean native steers. It is worthy to note that the protocol of Picard et al allowed a good separation of adult MyHCs but not of fetal and developmental MyHC isoforms (Figure b,c) compared to earlier protocols. , …”
Section: Techniques Allowing the Classification Of Muscle Fibersmentioning
confidence: 98%
“…As stated above, the contractile properties of a muscle could be further analyzed through electrophoretic separation (SDS-PAGE) of the different MyHC isoforms according to their molecular weights. However, these four different isoforms of MyHCs have close amino acid composition and consequently molecular weights (223.900, 224.243, 223.875, and 224.026 kDa for bovine MyHC I, IIa, IIx, IIb, respectively); hence, there is a difficulty to separate them with a high reproducibility . To avoid this, an accurate protocol was first proposed by Picard et al and another one recently by Scheffler et al to separate the different bovine MyHC isoforms in miniature polyacrylamide gels (Figure ).…”
Section: Techniques Allowing the Classification Of Muscle Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report, three myosin isoforms (myosin-1, -2, and -7) were identified from bovine longissimus muscle by analysis of LC-MS/MS ( Kim, 2014 ). However, additional analyses were needed because it was not confirmed whether myosin-4 existed in this muscle.…”
Section: Resultsmentioning
confidence: 99%